2006
DOI: 10.2337/diacare.29.02.06.dc05-1067
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function and Endocrine Profile in Fertile Women With Type 1 Diabetes

Abstract: OBJECTIVE -Aims of this study were 1) to assess sexual function and endocrine profile among fertile type 1 diabetic women during the follicular and luteal phases of the menstrual cycle, 2) to compare these results with those obtained among healthy fertile women who served as control subjects, and 3) to explore the correlations between sexual function and endocrine milieu among patients and control subjects during the follicular and luteal phases of the menstrual cycle.RESEARCH DESIGN AND METHODS -Fifty fertile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 25 publications
12
107
1
2
Order By: Relevance
“…On the other hand, decreased sexual function occurs independently of mood deflections, while the role of the endocrine milieu remains unclear. 7,18 In conclusion, we showed that in Italian otherwise healthy women with FSD obesity affects several aspects of sexuality. Interventional studies aimed at reducing body weight in women with FSD are needed to disclose a cause and effect relation between obesity and FSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, decreased sexual function occurs independently of mood deflections, while the role of the endocrine milieu remains unclear. 7,18 In conclusion, we showed that in Italian otherwise healthy women with FSD obesity affects several aspects of sexuality. Interventional studies aimed at reducing body weight in women with FSD are needed to disclose a cause and effect relation between obesity and FSD.…”
Section: Discussionmentioning
confidence: 99%
“…(3) We used a validated, internationally established questionnaire (FSFI) to assess the prevalence of sexual dysfunction, which was administered during the same phase of the cycle in order to avoid interference in the assessment of sexual function. 18 However, women above 60 years were not included in the study, and hormonal and mood assessments were not performed. On the other hand, decreased sexual function occurs independently of mood deflections, while the role of the endocrine milieu remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Also for diabetes mellitus, which represents an important causes of ED in men, 60 the data about the prevalence of FSD are controversial. [61][62][63] We found 64 a negative relationship between body weight and sexual function in 52 women with abnormal values of FSFI (score p23) (Figure 2). We also showed that obesity affects several aspects of sexual function in otherwise healthy women with FSD, including arousal, lubrication, satisfaction and orgasm, but not desire and pain.…”
Section: Obesity Metabolic Syndrome and Female Sexual Functionmentioning
confidence: 99%
“…Several studies have suggested that circulating estradiol concentrations are decreased in women with type 1 DM, [37][38][39] suggesting that diabetes may be associated with dysregulation of sex hormone biosynthesis. Similar observations were made in experimental models of type 1 DM.…”
Section: Nephropathy Sex Hormones and Diabetesmentioning
confidence: 99%